2011
DOI: 10.1002/hfm.20294
|View full text |Cite
|
Sign up to set email alerts
|

Integrating service quality evaluation model to improve employees' satisfaction for high‐tech iindustry

Abstract: This study addresses the deficiency research of service quality by integrating the importance–satisfaction model (I‐S model) and the performance control matrix to provide a more comprehensive assessment model for improving specific quality attributes. The study applies this integrated measuring instrument in a Taiwanese high‐tech industry by using a questionnaire survey of production‐line employees to assess importance and satisfaction in their capacity as internal customers of the company. The study thus iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This category of studies focuses on prioritizing service quality attributes using different decision-making matrices and measurements with alternatives and attributes (Chen 2011;Lin 2010). Shieh et al (2010) identified major criteria of hospital service quality and causal relationships among them in Taiwan using SERVQUAL.…”
Section: Hotel Service Qualitymentioning
confidence: 99%
“…This category of studies focuses on prioritizing service quality attributes using different decision-making matrices and measurements with alternatives and attributes (Chen 2011;Lin 2010). Shieh et al (2010) identified major criteria of hospital service quality and causal relationships among them in Taiwan using SERVQUAL.…”
Section: Hotel Service Qualitymentioning
confidence: 99%
“…From a service context, Chen () states that employee satisfaction has as great an influence on organizational performance as does customer satisfaction. Many studies identify job satisfaction as an antecedent of organizational commitment (e.g., Baroudi, ; Korunka, Hoonakker, & Carayon, ; Lum et al., ; Mueller & Price, ; Tett & Meyer, ; Wallace, ).…”
Section: Organizational Commitment and Job Satisfaction In The Hotel mentioning
confidence: 99%
“…Authors propose a five levels maturity model (Duffy, 2002) Table 2 shows these maturity levels and practices, and actions recommended to achieve level 1 and level 2 of the model (those are relevant to these paper). According to Chen exist a deficiency of service quality research and the relationship between quality attributes, the relative satisfaction level of the employees and the resources available for improvement these attributes (Chen, 2012). The model presented recognizes the importance of the HR view and the impact in service quality.…”
Section: Smesmentioning
confidence: 99%